Trichoderma longibrachiatum and Aspergillus fischeri Infection as a Cause of Skin Graft Failure in a Patient with Critical Burns after Liver Transplantation - Lipový, Břetislav; Raška, Filip; Kocmanová, Iva; Hanslianová, Markéta; Hladík, Martin; Holoubek, Jakub; Bezdíček, Matěj; Macháček, Ctirad (Journal of fungi (Basel, Switzerland), 2021)
Infectious complications are responsible for the majority of mortalities and morbidities of patients with critical burns. Although bacteria are the predominant etiological agents in such patients, yeasts and fungi have become relatively common causes of infections over the last decade. Here, we report a case of a young man with critical burns on 88% TBSA (total body surface area) arising as a part of polytrauma. The patient's history of orthotopic liver transplantation associated with the patient's need to use combined immunosuppressant therapy was an additional complication. Due to deep burns in the forearm region, we have (after a suitable wound bed preparation) applied a new bi-layered dermal substitute. The patient, however, developed a combined fungal infection in the region of this dermal substitute caused by Trichoderma longibrachiatum and Aspergillus fischeri (the first case ever reported). The infection caused the loss of the split-thickness skin grafts (STSGs); we had to perform repeated hydrosurgical and mechanical debridement and a systemic antifungal treatment prior to re-application of the STSGs. The subsequent skin transplant was successful.
Keywords: liver transplantation; immunosuppression; infection; dermal substitute; critical burns; Aspergillus; Trichoderma